Tonian deltaic and storm-influenced marine sedimentation on the edge of Laurentia: the Veteranen Group of northeastern Spitsbergen, Svalbard - Gibson, TM; Millikin, AEG; Anderson, RP; Myrow, PM; Rooney, AD; Strauss, JV (Elsevier, 2021)
The Hecla Hoek succession of northeastern Svalbard, Norway, is an ~7 km thick Tonian– Ordovician sedimentary succession that overlies Stenian–Tonian felsic igneous and metasedimentary rocks. The carbonate-dominated upper Tonian–Ediacaran (ca. 820–600 Ma) Akademikerbreen and Polarisbreen groups have yielded important insights into Earth’s Neoproterozoic climate, environment, and biological evolution. However, the underlying siliciclastic-dominated lower Tonian (ca. 950–820 Ma) Veteranen Group has garnered little attention despite the fact that it is remarkably well-preserved and hosts diverse microfossil assemblages. Here, we present the first detailed sedimentological analysis of the Veteranen Group from a continuous ~4.4 km thick stratigraphic section at Faksevågen, Ny Friesland, Spitsbergen. Integrated facies analysis, sequence stratigraphy, and carbonate δ13Ccarb and δ18 Ocarb chemostratigraphy elucidate the early depositional history of the Hecla Hoek basin and provide fundamental paleoenvironmental constraints for future investigations of this succession as an archive of Tonian Earth History. The Veteranen Group records a long-lived deltaic and storm influenced marine sedimentary system that reveals dynamics of Precambrian clastic sedimentation prior to the evolution of land plants. Five asymmetric transgressive-regressive (T-R) sequences within the Veteranen Group thin upwards, providing support for the hypothesis that the contact with the Akademikerbreen Group represents a rift-to-drift transition. This complex record of Tonian deltaic and storm-influenced marine sedimentation along the Laurentian margin strengthens correlation between the Veteranen Group and coeval strata from East Greenland and sets the stage to better understand the Proterozoic tectonic evolution of the North Atlantic–Circum34 Arctic region following the Grenville orogeny.